Analysis of Economic Growth, Education, Labor Participation, and Minimum Wage on Open Unemployment in Malang - M. Dikri Khoirul Ibad; Niniek Imaningsih (Finance : International Journal of Management Finance, 2026)
This study investigates the determinants of the open unemployment rate in Malang City, where unemployment remains a major challenge despite ongoing regional economic development. The study aims to analyze the effects of economic growth, education level, labor force participation rate, and minimum wage on the open unemployment rate during the 2008–2024 period. Using a quantitative approach, this research applies multiple linear regression analysis based on secondary data obtained from the Central Statistics Agency (BPS) and related institutions. Hypothesis testing was conducted through the t-test, F-test, and coefficient of determination (R²). The findings reveal that economic growth and minimum wage have a negative and significant effect on the open unemployment rate, indicating that higher economic growth and appropriate wage policies contribute to reducing unemployment in Malang City. In contrast, education level and labor force participation rate do not show a significant effect on unemployment. Simultaneously, all independent variables significantly influence the open unemployment rate. These findings imply that policies promoting sustainable economic growth and effective minimum wage regulations can serve as important instruments in reducing unemployment and supporting regional economic development in Malang City.